2023
DOI: 10.2196/38298
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Evaluating a Measure of the Willingness to Use Pandemic-Related mHealth Tools Using National Probability Samples in the United States: Quantitative Psychometric Analyses and Tests of Sociodemographic Group Differences

Abstract: Background There are no psychometrically validated measures of the willingness to engage in public health screening and prevention efforts, particularly mobile health (mHealth)–based tracking, that can be adapted to future crises post–COVID-19. Objective The psychometric properties of a novel measure of the willingness to participate in pandemic-related screening and tracking, including the willingness to use pandemic-related mHealth tools, were tested.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…The present psychometric evaluation indicated that the COVID-19-related psychological distress measure was assessing the same construct in heterosexual participants and sexual minority participants. A previous study has already validated the psychometric properties of the present items (eg, construct validity and internal consistency) and demonstrated measurement invariance across age groups, genders, and races and ethnicities [28]. Other studies on willingness to use digital health tools have typically used a single item [63] or several items treated as separate measures [68,69] rather than a single, validated scale.…”
Section: Overviewmentioning
confidence: 84%
See 2 more Smart Citations
“…The present psychometric evaluation indicated that the COVID-19-related psychological distress measure was assessing the same construct in heterosexual participants and sexual minority participants. A previous study has already validated the psychometric properties of the present items (eg, construct validity and internal consistency) and demonstrated measurement invariance across age groups, genders, and races and ethnicities [28]. Other studies on willingness to use digital health tools have typically used a single item [63] or several items treated as separate measures [68,69] rather than a single, validated scale.…”
Section: Overviewmentioning
confidence: 84%
“…Based on the established definitions of a disparity [61,62] and the analytic framework of intersectionality theory [32,33,59], this study detected no referent disparity based on sexual orientation and no joint or excess joint disparity at the intersection of sexual orientation identity and other demographic characteristics. A previous study that used the same publicly available data without testing for sexual minority status as a predictor or moderator found no significant associations that would indicate an age-related, gender, or racial or ethnic disparity [28]. In contrast to other studies, which showed mixed findings for race or ethnicity and other demographics as a predictor without considering sexual minority status [26,27,[29][30][31], the significant main effects of race or ethnicity in this study occurred among heterosexual adults in the presence of interactions of race or ethnicity with sexual minority status.…”
Section: Overviewmentioning
confidence: 94%
See 1 more Smart Citation